Gravity models: A tool for migration analysis - Raul Ramos (IZA World of Labor, 2016)
Gravity models have long been popular for analyzing economic phenomena related to the movement of goods and services, capital, or even people; however, data limitations regarding migration flows have hindered their use in this context. With access to improved bilateral (country to country) data, researchers can now use gravity models to better assess the impacts of migration policy, for instance, the effects of visa restriction policies on migration flows. The specification, estimation, and interpretation of gravity models are illustrated in different contexts and limitations of current practices are described to enable policymakers to make better informed decisions.
Keywords: F22; J11; J61; C33; C53; 330; gravity models; international migration; migration determinants; migration policies